2015
DOI: 10.1177/0042098015580899
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual determinants of victimisation in Brazilian urban centres: A multilevel approach

Abstract: This article analyses the influence of both contextual and individual urban characteristics on violence victimisation in Brazilian cities. A multilevel approach is used to capture the effects of the urban contextual variables with respect to the probability of becoming a robbery victim in Brazilian urban centres. The results demonstrate that factors associated with social context, such as proportions of cities’ recent migrants or female-headed households, affect victimisation, as do individual characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Also, like others, we do find a strong positive impact on youth crime of the level of urbanization, which is consistent with the idea that urban environments are more conducive to violent crime (e.g. Moura and Silveira Neto, 2016; Urdal and Hoelscher, 2012). The variable capturing the timing of elections is associated with fewer crime incidents during the run-up toward governor elections.…”
Section: Resultssupporting
confidence: 92%
“…Also, like others, we do find a strong positive impact on youth crime of the level of urbanization, which is consistent with the idea that urban environments are more conducive to violent crime (e.g. Moura and Silveira Neto, 2016; Urdal and Hoelscher, 2012). The variable capturing the timing of elections is associated with fewer crime incidents during the run-up toward governor elections.…”
Section: Resultssupporting
confidence: 92%
“…This process was strengthened by the spillover effects caused by a better educated workforce, the fact that knowledge accumulated in one city may also benefit neighbouring cities, a result that up to now has not been documented in the literature. Similarly, the negative effects on the growth of cities' populations due to growing population density and homicide rates, not only in the cities themselves but also due to spillover effects in their surroundings, are entirely consistent with the negative impacts on well-being arising from the congestion of public spaces, deficient urban infrastructures (which, for example, explain the very high commuting time of Brazilian urban centres) and the increased urban violence experienced by Brazilian cities during the last decades (Moura and Silveira Neto, 2015).…”
Section: Determinants Of Brazilian Population Dynamicssupporting
confidence: 61%
“…Even the "Moving to Opportunity" (MTO) experiment in Boston found that the relocation of young people living in poverty to higher-income neighbourhoods, exposed to less contextual violence, reduced their chances of victimization and improved their perception of security (Katz et al, 2001). However, another study in Brazil found that the highest probability of victimization does not occur among the poorest, but in young people with medium income and higher education, who spend more time on public transport (Moura and Neto, 2015).…”
Section: Resultsmentioning
confidence: 99%